2004
DOI: 10.1080/10428190310001623856
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic, Non-Secretory Multiple Myeloma

Abstract: A 70-year-old woman presented with pancytopenia associated with plasma cell infiltration of her bone marrow. The plasma cells were often multinucleated and demonstrated phagocytosis of erythroid and granulocytic cells. Atypical immunophenotypic features included the expression of CD117 and CD13 and the lack of expression of CD56. Although kappa chains were demonstrable in the cytoplasm, no paraprotein was found in the serum or urine. Osteolytic lesions were absent. The pancytopenia of this unusual patient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Hemophagocytosis of malignant cells occurs in acute lymphoblastic leukemia, chronic myeloid leukemia in blast crisis, metastatic carcinoma, hairy cell leukemia, multiple myeloma, and AML with t(8;16) [13][14][15][16][17][18]. In this study, we frequently observed leukemic cells showing the hemophagocytosis of erythrocytes, granulocytes, and platelets and vacuolation in AML with t(16;21).…”
Section: Discussionmentioning
confidence: 73%
“…Hemophagocytosis of malignant cells occurs in acute lymphoblastic leukemia, chronic myeloid leukemia in blast crisis, metastatic carcinoma, hairy cell leukemia, multiple myeloma, and AML with t(8;16) [13][14][15][16][17][18]. In this study, we frequently observed leukemic cells showing the hemophagocytosis of erythrocytes, granulocytes, and platelets and vacuolation in AML with t(16;21).…”
Section: Discussionmentioning
confidence: 73%
“…The mechanism of hemophagocytosis in multiple myeloma is unclear, as plasma cells have no phagocytic function under normal circumstances. Results of the direct antiglobulin test in humans are almost always negative, suggesting hemophagocytosis by neoplastic cells is not an autoimmune function 14 . It has been speculated that phagocytic plasma cells may arise by expansion of a rare B‐cell clone with innate phagocytic potential 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Results of the direct antiglobulin test in humans are almost always negative, suggesting hemophagocytosis by neoplastic cells is not an autoimmune function 14 . It has been speculated that phagocytic plasma cells may arise by expansion of a rare B‐cell clone with innate phagocytic potential 14 . A single case of phagocytic plasma cells aberrantly expressing CD15 (normally found on neutrophils and monocytes and involved in phagocytosis) has been reported in people 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cats, erythrophagocytosis by neoplastic plasma cells [32], mast cells [133]), lymphocytes [134][135] and histocytes [136] has been observed. In the same way, there are several reports of phagocytic plasma cells in people with MM [137]. Although erythrophagocytic plasma cells in humans with MM are rare, neoplastic plasma cells have been observed with phagocytosed platelets and granulocytes [138].…”
Section: Hematologymentioning
confidence: 81%